Revisiting Top-Down Primary Stress - Kathryn Pruitt (Universitat Autònoma de Barcelona, 2019)
Metrical theory recognizes differences between primary and non-primary stresses, sometimes within the same language. In serial theories, this has often led to a parametric approach in derivation: some languages are ‘top-down’, with the primary stress assigned first, while other languages are ‘bottom-up’, where foot construction precedes primary stress placement. This paper examines two languages (Cahuilla and Yine) that have be treated as ‘top-down’ in rulebased metrical theory, and it shows that neither requires a top-down analysis in Harmonic Serialism, a derivational version of Optimality Theory. On the basis of these case studies it is argued that the common, intuitive notion of what makes a language ‘top-down’—a primary stress’s independence from non-primary stresses—is oversimplified. The case studies reveal the importance of theoretical framework and typological predictions in establishing the order of primary and non-primary stress assignment. The argument culminates in a concise statement of Harmonic Serialism-specific criteria for establishing that a top-down derivation is required.